A Review on Mobile Cloud Computing (International Journal of Engineering and Computer Science, 2017)
Mobile Cloud computing is the ability of cloud computing services in the environment of mobile by providing different and optimal services for mobile users. Mobile Cloud Computing incorporates all elements of mobile networks and cloud computing. In MCC data and computing modules can be processed in the cloud and mobile device have no need to do configuration like memory capacity, CPU speed etc. However mobile device facing up many struggles in their resources like privacy, mobility and security. These challenges have large affect in the improvement of service qualities of MCC. In this paper, we discuss the review on MCC technologies and its architecture, characteristics, applications, advantages, limitations and offloading techniques of mobile cloud computing.